Approach to Identifying Causative Pathogens of Community-Acquired Pneumonia in Children Using Culture, Molecular, and Serology Tests - Mardian, Yan; Menur Naysilla, Adhella; Lokida, Dewi; Farida, Helmia; Aman, Abu Tholib; Karyana, Muhammad; Lukman, Nurhayati; Kosasih, Herman; Kline, Ahnika; Lau, Chuen-Yen (Frontiers in Pediatrics, 2021)
Determining the causative pathogen(s) of community-acquired pneumonia (CAP) in children remains a challenge despite advances in diagnostic methods. Currently available guidelines generally recommend empiric antimicrobial therapy when the specific etiology is unknown. However, shifts in epidemiology, emergence of new pathogens, and increasing antimicrobial resistance underscore the importance of identifying causative pathogen(s). Although viral CAP among children is increasingly recognized, distinguishing viral from bacterial etiologies remains difficult. Obtaining high quality samples from infected lung tissue is typically the limiting factor. Additionally, interpretation of results from routinely collected specimens (blood, sputum, and nasopharyngeal swabs) is complicated by bacterial colonization and prolonged shedding of incidental respiratory viruses. Using current literature on assessment of CAP causes in children, we developed an approach for identifying the most likely causative pathogen(s) using blood and sputum culture, polymerase chain reaction (PCR), and paired serology. Our proposed rules do not rely on carriage prevalence data from controls. We herein share our perspective in order to help clinicians and researchers classify and manage childhood pneumonia.